PEMBERDAYAAN KADER POSBINDU LANSIA SEBAGAI UPAYA PENINGKATAN KUALITAS HIDUP LANSIA DI DESA KANGKUNG DEMAK - Yunie Armiyati; Edy Soesanto; Tri Hartiti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
An increasing number of elderly people will have an impact on the socioeconomic well in the family, society and the government. The aging process resulted in a decrease in the physical, psychological, decreased independence, inability to work and the impact on the non-fulfillmentof their daily needs and social needs of the community. Posbindu as an effort to empower elderly people to optimize promotive, preventive, curative and rehabilitative for the problems of the elderly need to engage in activities that can support these efforts through posyandu elderly,providing support to the elderly and to optimize the utilization of plant family medicine for curative measures for the health problems of the elderly. Support for improving community participation in pokjakes and optimizing health worker roles and community service activities conducted through science and technology-based community empowerment elderly health cadres. The purpose of this community service activities was to apply science and technology to the community-based elderly health cadres. Activities undertaken include the making of a media health promotion leaflets and flipcharts, conducting a training cadre posyandu elderly health prevention and treatment of diseases of the elderly, physical examination and simple laboratory tests in the elderly, as well as the management of complementary therapies in elderly empower the community in producing extracts family of traditional medicine in the packaging. Other activities carried out by holding the equipment to cultivate medicinal plants, medicinal plants cultivation training and training of traditional medicine-making family. Having done community service activities, increased numbers of cadres and cadres liveliness, increasedtraffic posbindu elderly and increased knowledge and skills in the management of elderly health problems as well as increase the ability of cadres in the processing of herbal ingredients.